Comparison between traditional strength training and complex contrast training on repeated sprint ability and muscle architecture in elite soccer players - Spineti, J.; Figueiredo, T.; Bastos De Oliveira, V.; Assis, M.; Fernandes De Oliveira, L.; Miranda, H.; Machado De Ribeiro Reis, V. M.; Simão, R. (The Journal of Sports Medicine and Physical Fitness, 2016)
BACKGROUND: The purpose of this study was to compare traditional strength training (TST) and complex contrast training (CCT) on the repeated-shuttle-sprint ability (RSSA), the countermovement squat jump (CMJ) height, the one repetition maximum (1RM) at squat on the Smith machine, and on muscle architecture in young, male elite soccer players.